2017
DOI: 10.1007/s13344-017-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the helical strake cross-section shape on vortex-induced vibrations suppression for a long flexible cylinder

Abstract: An experimental study on a bare flexible cylinder as well as cylinders fitted with two types of cross-sectioned helical strakes was carried out in a towing tank. The main purpose of this paper is to investigate the effects of strakes' crosssection on the vortex-induced vibrations (VIV) suppression of a flexible cylinder. The square-sectioned and roundsectioned helical strakes were selected in the experimental tests. The uniform current was generated by towing the cylinder models along the tank using a towing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In Figure 6c, the dominant frequency is 6.50 Hz, which is corresponding to the second-order mode. Moreover, only one strong frequency peak is observed with U = 0.75 m/s and T = 300 N. This trend of displacement response is consistent with that of a flexible cylinder with relatively high mass ratio undergoing VIV [21,26,28]. Figure 7 plots the maximum CF displacement against the reduced velocity Vr = U/f1D (where f1 is the fundamental frequency of the pipe model in water).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…In Figure 6c, the dominant frequency is 6.50 Hz, which is corresponding to the second-order mode. Moreover, only one strong frequency peak is observed with U = 0.75 m/s and T = 300 N. This trend of displacement response is consistent with that of a flexible cylinder with relatively high mass ratio undergoing VIV [21,26,28]. Figure 7 plots the maximum CF displacement against the reduced velocity Vr = U/f1D (where f1 is the fundamental frequency of the pipe model in water).…”
Section: Resultssupporting
confidence: 75%
“…Therefore, a reconstruction algorithm based on the model analysis technique was adopted. It was originally proposed by Lie and Kaasen [27] and subsequently applied in the experimental works of [16,17,[21][22][23][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The influences of the different cross-section shapes of helical strakes are different but moderate [122,128] .…”
Section: Helical Strakementioning
confidence: 99%
“…It was proved by investigating the vorticity, Reynolds stress and turbulent energy of the flow field that arranging a water droplet-shaped mesh structure around the cylinder suppresses the formation of a vortex during the flow around the cylinder. Xu et al [13] performed VIV suppression research on the cylindrical surfaces with square columns or circular columns and found that the columns of square and circular structures were greatly reduced in a strain, displacement amplitude and mean frequency. Yu et al [14] analyzed the influence of different chamfering radii on the flow around the square column.…”
Section: Introductionmentioning
confidence: 99%